Appraising the uptake and use of the IDEAL Framework and Recommendations: A review of the literature. (September 2018) - Khachane, Asha; Philippou, Yiannis; Hirst, Allison; McCulloch, Peter
Abstract: Introduction: Evaluation of new surgical innovations is complex and variably regulated, and historically the quality of surgical studies has been criticized. The IDEAL (Idea, Development, Exploration, Assessment, Long-term monitoring) Framework was established to provide a pathway for evaluating surgical innovations at each stage of their development in order to produce high quality surgical research. Since the inception of IDEAL in 2009, there has been no assessment of its use. In this review, we look at the uptake and usage of IDEAL by examining the published literature. Methods: We conducted a literature search to identify all of the publications that cited IDEAL and included only those papers that intentionally used IDEAL as part of the study methodology. We then characterized these publications by year of publication, specialty, and geographical location. We performed a critical appraisal of Stage 1, 2a, and 2b studies in order to assess the degree to which authors have correctly followed the Framework and Recommendations. Results: We found 790 citations of IDEAL publications, and after abstract and full-text screening, 38 prospective studies for a surgical innovation that used IDEAL remained. We saw an overall increase in the uptake of IDEAL, with a predominance in urology and origin in the United Kingdom. The critical appraisal showed that although authors identified their project as using IDEAL, they often failed to include key IDEAL characteristics; this was especially true for the features unique to IDEAL Stages 2a and 2b. Conclusion: It is evident from the large number of studies citing IDEAL that the importance and challenges of reporting surgical research is well recognized among researchers. There is growing enthusiasm for using IDEAL but the current level of understanding of the Recommendations is low. Clearer and more comprehensive explanation of the application of the IDEAL Framework and Recommendations is needed to guide surgical researchers undertaking IDEAL based studies of surgical innovations. Highlights: IDEAL was introduced in 2009 to improve the quality of surgical research. This is the first review of its uptake and assessment of its use in the literature. There has been an upward trend in the use of IDEAL since 2009. Authors tend to omit key features of the IDEAL Stages. This shows where clarification is needed when undertaking IDEAL studies.